Optimum ratio of compressed biomethane gas as dual fuel in turbocharged common rail diesel engine - Niti Kammuang-lue (2018)
© 2017 Energy Institute. During the world faced a crude oil price crisis, the selling price of all fuel types increased considerably. Commercial carriers that use vehicles installed with the turbocharged common rail diesel engine (TCRD Engine) attempted to find methods to reduce the fuel cost. One of the many alternative methods was the use of compressed biomethane gas (CBG) together with diesel, which was called as the dual fuel. In general, the amount of CBG supplied into the engine is mostly adjusted to be in the highest ratio without taking care of the influences on the engine and the environment. In order to introduce a guideline to adjust the CBG dual fuel correctly, this study has been conducted with objectives as follows: (i) to study the optimum ratio of CBG on unmodified TCRD engine, (ii) to describe the effect of critical factors on the optimum duration of CBG injection, and (iii) to analyze the fuel cost and the economical break-even point. The test was conducted on a 2.5L, four-cylinder, four-stroke, TCRD Engine in which the crankshaft end was coupled to the hydraulic dynamometer for measuring and controlling the torque to be constant as the reference torques obtained from the use of the pure diesel. The study found that the trend of variation in the optimum ratio of CBG significantly depended on the trend of the optimum duration of CBG injection, that is, increasing in low engine speed ranges, being constant at relatively high values during medium to high engine speeds, and, finally, decreasing to reach the lowest at the highest engine speed that the CBG can be supplied safely. The critical factors to define the optimum ratio of CBG consisted of smoke opacity in exhaust gas, exhaust gas temperature, and engine knock, which dominated differently for each of the different values of engine speed and torque. The analysis on fuel consumption and fuel cost showed that although the brake specific fuel consumption (BSFC) of the CBG and diesel dual fuel was higher than that of diesel, the fuel cost of the dual fuel was less than that of diesel because of the lower price of the CBG. This study also presented that CBG could be safely used as a dual fuel in unmodified TCRD engines if suitable critical factors to limit the optimum ratio of CBG were defined. Moreover, CBG was confirmed as suitable for use as the dual fuel with diesel without modification of the engine except the installation on the gas supply system. Therefore, these results can be followed to promote a decrease in the overall cost in the use of the TCRD engine in commercial transportation with high effectiveness and safety to the engine and the environment.